Extracellular Vesicles from Human Urine-Derived Stem Cells Ameliorate Particulate Polyethylene-Induced Osteolysis - Li H (Dove Medical Press, 2021)
Hui Li,1,2,* Xiao-Lei Fan,1,2,* Yi-Nan Wang,1,2 Wei Lu,1,2 Haoyi Wang,1,2 Runzhi Liao,1,2 Min Zeng,1,2 Jun-Xiao Yang,1,2 Yihe Hu,1,2 Jie Xie1,2 1Department of Orthopedics, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 2Hunan Engineering Research Center of Biomedical Metal and Ceramic Implants, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jie Xie; Yihe HuDepartment of Orthopedics, Xiangya Hospital, Central South University, #87 Xiangya Road, Changsha, Hunan, 410008, People’s Republic of ChinaTel +86– 731– 89753006; +86– 731– 89753706Email dr_xiejie@163.com; csuhuyihe@163.comPurpose: Wear debris particle-induced periprosthetic osteolysis is a severe complication of total joint replacement that results in aseptic loosening and subsequent arthroplasty failure. No effective therapeutic agents or drugs have been approved to prevent or treat osteolysis; thus, revision surgery is often needed. Extracellular vesicles (EVs) are vital nanosized regulators of intercellular communication that can be directly applied to promote tissue repair and regeneration. In this study, we assessed the therapeutic potential of EVs from human urine-derived stem cells (USCs) (USC-EVs) in preventing ultrahigh-molecular-weight polyethylene (UHMWPE) particle-induced osteolysis.Methods: USCs were characterized by measuring induced multipotent differentiation and flow cytometry. USC-EVs were isolated and characterized using transmission electron microscopy (TEM), dynamic light scattering (DLS) and Western blotting. RAW264.7 cells and bone marrow mesenchymal stem cells (BMSCs) were cultured with USC-EVs to verify osteoclast differentiation and osteoblast formation, respectively, in vitro. The effects of USC-EVs were investigated on a UHMWPE particle-induced murine calvarial osteolysis model by assessing bone mass, the inflammatory reaction, and osteoblast and osteoclast formation.Results: USCs differentiated into osteogenic, adipogenic and chondrogenic cells in vitro and were positive for CD44, CD73, CD29 and CD90 but negative for CD34 and CD45. USC-EVs exhibited a cup-like morphology with a double-layered membrane structure and were positive for CD63 and TSG101 and negative for calnexin. In vitro, USC-EVs promoted the osteogenic differentiation of BMSCs and reduced proinflammatory factor production and osteoclastic activity in RAW264.7 cells. In vivo, local injection of USC-EVs around the central sites of the calvaria decreased inflammatory cytokine generation and osteolysis compared with the control groups and significantly increased bone formation.Conclusion: Based on our findings, USC-EVs prevent UHMWPE particle-induced osteolysis by decreasing inflammation, suppressing bone resorption and promoting bone formation.Keywords: extracellular vesicles, urine-derived stem cells, UHMWPE, wear particle-induced osteolysis, anti-inflammatory